RFID and supply chain performance: adoption issues in the retail supply chain. (10th December 2007) - Waters, Stephen; Rahman, Shams-ur
Using case studies and two mini surveys within the Australian retail supply chain sector this study identifies four categories of factors which impact RFID technology adoption. These are technological, economic, organisational, and external factors. Incorporating these factors the paper suggests an AHP-based conceptual framework to study the adoption process in a more systematic manner.